Catechetical formation program for religion teachers of the Diocese of Ubonratchathani, Thailand - Thongmak, Victor Khamdee (Animo Repository, 2010)
The main objective of this study is the formulation of a Religion Teachers’ Formation Program based on the ecclesiological themes of the Vision of the Diocese of Ubonratchathani, Thailand which states that the local Church of the Diocese of Ubonratchathani is a community united in God’s love, a community of followers, a community of servants, and a community of evangelizers who proclaim the Kingdom of God to all peoples. The study applied a descriptive analytical approach in the examination of Church documents, books, issues and other materials relevant to this study. The conceptual framework for the Catechetical Formation Program of Religion Teachers integrates the Diocesan Vision of Ubonratchathani, Thailand which also serves as the ground for the formulation of the catechetical formation program. Using the ARA Model or Activity-Reflection in faith-Action Model of Neo (1988) for the formulation of the proposed formation program, this study views the formation program as an implementation of that vision in the catechetical field and a response to the need of the Church, especially of the Diocese of Ubonratchathani for training of the religion teachers. The formation program consists of four modules which, as mentioned, are based on the four ecclesiological themes of the Diocesan Vision: 1) the Church as a community united in God’s love; 2) the Church as a community of followers; 3) the Church as a community of servants; and 4) the Church as a community of evangelizers. The proposed formation program consists of 24 sessions. Each session is good for three to four hours and may be implemented yearly in various parishes where the religion teachers live. This formation program offers basic initial training for the religion teachers of the Diocese of Ubonratchathani, and this can be further enriched by other formation programs and by regular evaluation to check its effectiveness